Is the Agency Assumption Valid for Public Corporations? - Sayre, Todd L.; Graham, Carol M. (Journal of Management Policy and Practice, 2018)
Friedman (1970) stated that CEOs of public corporations are the agents of shareholders, which we refer to as the ‘agency assumption.’ Jensen and Meckling (1976) modeled Friedman’s agency assumption, popularizing it among academics. However, in the mid-1970s, the academic consensus was that the agency assumption had little predictive validity in that CEOs did not generally maximize profits for shareholders (Fama & Miller 1972; Jensen & Walkling 2010). Post-1990s the prescriptive validity of the agency assumption improved with the widespread adoption of executive stock option pay. The purpose of this paper is to determine whether the agency assumption is descriptively and prescriptively valid.